Use of Remote Lab for Online and Real time Practicum At Vocational School in Indonesia - Jaya, Hendra; Haryoko, Sapto; Taris, Lumu; Ida, Putri (International Journal of Online and Biomedical Engineering (iJOE), 2020)
The Aims of this paper is to analyze the influence of Remote Lab on overcoming the limitation of practicum facilities. This study uses qualitative research methods. In this study, the researchers conducting a study of the use of remote labs in overcoming the unavailability of laboratory equipment. 1). The completeness of practicum equipment available at SMKs is still inadequate, only around 30%. Some students stated that when carrying out practical activities, each tool used by 4 students simultaneously made the practicum process not run effectively and often there was discrimination only intelligent students who could complete the sequence, then some students also stated that the existing components many have been damaged. Another statement expressed by students that not all productive subjects can be practiced because of limited equipment that can be caused by several factors including: a) inadequate school budget; b) tools and practice materials that are difficult to obtain; 2) The Remote LAB application sends data at any time when selecting a Lab, selecting a Gate, and selecting input from a gate. The output of the gate will be measured using a multi-meter and oscilloscope and will be monitored directly via YouTube streaming, so that it can be monitored in real time on the Remote LAB Android application; 3) Practical experience does not have to be identical in a laboratory room on a supervised Schools. Students receive tangible observations using real equipment to arrive at concrete conclusions, as well as assessing them in a physical laboratory with equipment so that it will be beneficial to improve their laboratory abilities.